The Role of Single Fathers in the Moral Development of Children Aged 5-6 Years - Yuliana, Yanda; Busyro Karim, Muhammad (Nak-Kanak: Journal of Child Research, 2024)
This study aims to explore the role of single fathers in the moral development of children aged 5-6 years in Nguwok Village, where morality is considered a crucial aspect of human development and life. The research method employed is qualitative with a descriptive approach. The subjects of this study are two single fathers with children aged 5-6 years residing in Nguwok Village, Modo District, Lamongan Regency. Data collection techniques include interviews, observations, and documentation, with data analysis following the Milles and Huberman model. The findings from this research indicate that single fathers play a significant role in nurturing their children, including bathing, feeding, and assisting with homework. The second role involves providing education, particularly in moral values, the third is acting as a mentor, which includes accompanying and disciplining the children, and the last role is that of a friend, ensuring the child feels comfortable talking or sharing stories with their father. According to the research results, the moral development of children raised by single fathers shows a balanced development between capability and incapability. The aspects of moral development examined include speaking politely, practicing religious worship, expressing gratitude when receiving something, maintaining personal and environmental cleanliness, and apologizing when making mistakes.